"Looking at him, how it hurt": Tsiolkas's Merciless Gods and Conjectural Literary Space. Issue 1 (2nd January 2022) - Birns, Nicholas
ABSTRACT: The short stories in Christos Tsiolkas's Merciless Gods (2014) offer perhaps his most complete and comprehensive portrait of the contemporary world. This assertion goes against conventional wisdom, especially in postcolonial literature, where the novel has long been a privileged form of speaking truth from the periphery to the centre, and in Australian literature, where what Timothy Brennan calls the "national longing for form" has typically dictated generic decisions. Tsiolkas achieves a greater coverage through fragmentation than through an ambitious total novel, particularly because of the juxtaposition of shocking detail and a fundamental and wholesome valuation of life. This valuation, however, is explicable by queer and post-political theorists such as Judith Butler, Wendy Brown and Jasbir Puar, and does not try to reconstitute a world anterior to difference and globalisation. Tsiolkas, while shocking the reader, also provides a conjectural affirmation of a plural Australia.